Light Activated Drug Delivery System: A Novel Approach for Controlled and Targeted Therapy - Amol S. Rone; Mrs. Rupali G. Chaudhari; Dr. P. N. Sable (International Journal of Advanced Research in Science Communication and Technology, 2026)
Light-Activated Drug Delivery Systems (LADDS) are advanced drug delivery systems that release drugs only when exposed to a specific wavelength of light. Unlike conventional drug delivery, which often causes uncontrolled drug release and systemic side effects, LADDS provide targeted and controlled drug release at the desired site and time. These systems use photoresponsive carriers such as liposomes, nanoparticles, hydrogels, and micelles, which respond to ultraviolet (UV), visible, or near-infrared (NIR) light. Light activation triggers mechanisms such as photo-cleavage, photo-isomerization, and photothermal effects, resulting in precise drug release. LADDS have promising applications in cancer therapy, dermatology, ophthalmology, gene delivery, and photodynamic therapy. Although challenges such as limited tissue penetration, high cost, and formulation complexity remain, ongoing advances in nanotechnology and photoresponsive materials are improving their clinical potential. Overall, light-activated drug delivery represents a promising strategy for safe, effective, and site-specific drug delivery